2012
DOI: 10.1002/adsc.201100424
|View full text |Cite
|
Sign up to set email alerts
|

Palladacycle‐Catalyzed Tandem Allylic Amination/Allylation Protocol for One‐Pot Synthesis of 2‐Allylanilines from Allylic Alcohols

Abstract: An efficient methodology involving the predominant formation of C À C bonds is described for the first direct synthesis of 2-allylanilines from allylic alcohols via a one-pot tandem allylic amination/allylation protocol catalyzed by a palladacycle under mild conditions without the requirement for additional activators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…The formation of 2‐ and 4‐allylanilines has been less studied. To the best of our knowledge, the formation of 2‐allylanilines ( via allylic substitution of alcohols with anilines) has been achieved using Cu(OTf) 2 , Re 2 O 7 , a palladacycle and iron‐based imidazolium salts (IBLAILs), while the synthesis of 4‐allylanilines has only been reported using Cu(OTf) 2 . A carboxylic acid functionalized graphene oxide and a cubane‐type sulfido cluster incorporating palladium and molybdenum have also been used for the synthesis of 4‐allylanilines, starting from N , N ‐dialkyl substituted anilines, which rules out the possibility of the aniline acting as N‐nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of 2‐ and 4‐allylanilines has been less studied. To the best of our knowledge, the formation of 2‐allylanilines ( via allylic substitution of alcohols with anilines) has been achieved using Cu(OTf) 2 , Re 2 O 7 , a palladacycle and iron‐based imidazolium salts (IBLAILs), while the synthesis of 4‐allylanilines has only been reported using Cu(OTf) 2 . A carboxylic acid functionalized graphene oxide and a cubane‐type sulfido cluster incorporating palladium and molybdenum have also been used for the synthesis of 4‐allylanilines, starting from N , N ‐dialkyl substituted anilines, which rules out the possibility of the aniline acting as N‐nucleophile.…”
Section: Introductionmentioning
confidence: 99%
“…The reactions catalyzed by Yb(OTf) 3 and Ce(OTf) 3 gave no desired product (entry 5). Similarly, the use of Fe(OTf) 3 , Cu(OTf) 2 or Nd(OTf) 3 gave low yields (entries [6][7][8]. Interestingly, I 2 combined with Fe(OTf) 3 successfully promoted the reaction to deliver a 75 % yield of 4 a (entry 9), while I 2 /Yb(OTf) 3 was not a good catalyst (entry 10).…”
Section: Resultsmentioning
confidence: 99%
“…The importance of allyl amine derivatives [1] for the synthesis of pharmaceuticals [2] and fine chemicals [3] has attracted considerable interest. In the last decade, most well-established methods for the synthesis of allyl amines and related compounds rely on the transition-metal-catalyzed [4] allylic amination of allyl alcohols [5][6][7][8] and their derivatives. [9][10][11][12] Palladium-catalyzed intraand intermolecular oxidative allylic aminations of non-activated alkenes have been shown an efficient approach to allyl amines in some systems.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Recently, we reported that the chiral cyclopalladated naphthylamine complex could be used to catalyse the P-H bond addition reaction to produce a series of enantiomerically pure functionalised mono-and diphosphanes. [6] Electronically, the naphthyl and benzyl complexes are similar. [6] Electronically, the naphthyl and benzyl complexes are similar.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that the chiral cyclopalladated naphthyl amine complex could be used to catalyse the P–H bond addition reaction to produce a series of enantiomerically pure functionalised mono‐ and diphosphanes 5. On the other hand, a simple ortho ‐palladated benzyl amine complex was found to be a highly efficient catalyst for the chemoselective C–C bond formation in the synthesis of 2‐allylanilines from allylic alcohols 6. Electronically, the naphthyl and benzyl complexes are similar 7,8.…”
Section: Introductionmentioning
confidence: 99%